2022
DOI: 10.3390/nu14122509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calorie Restricted Diet on Oxidative/Antioxidative Status Biomarkers and Serum Fibroblast Growth Factor 21 Levels in Nonalcoholic Fatty Liver Disease Patients: A Randomized, Controlled Clinical Trial

Abstract: Oxidative stress plays a fundamental role in the development and progression of nonalcoholic fatty liver disease (NAFLD). This study aimed to investigate the effects of a calorie-restricted (CR) diet on oxidative/anti-oxidative status in patients with NAFLD and the potential mediating role of fibroblast growth factor 21 (FGF-21) in this regard. This randomized, controlled clinical trial was carried out on sixty patients with NAFLD aged 20 to 60 years with body mass index (BMI) ranging from 25 to 35 kg/m2. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Despite substantial weight loss of 7.3 kg on average and concomitant health improvements [ 32 ], 12 weeks of 25% energy reduction did not affect fasting FGF21 levels. Previous weight loss trials have reported conflicting findings, with some trials reporting a reduction in fasting FGF21 levels upon diet-induced weight loss [ 9 , 10 , 11 , 12 , 13 ], and others reporting an increase [ 40 ] or no effect on circulating FGF21 levels [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Generally, the studies that report a change in plasma fasting FGF21 were performed in individuals with more severely impaired metabolic health (e.g., T2DM, NAFLD, morbid obesity), who typically have elevated FGF21 levels and thus more room for improvement compared to individuals in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite substantial weight loss of 7.3 kg on average and concomitant health improvements [ 32 ], 12 weeks of 25% energy reduction did not affect fasting FGF21 levels. Previous weight loss trials have reported conflicting findings, with some trials reporting a reduction in fasting FGF21 levels upon diet-induced weight loss [ 9 , 10 , 11 , 12 , 13 ], and others reporting an increase [ 40 ] or no effect on circulating FGF21 levels [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Generally, the studies that report a change in plasma fasting FGF21 were performed in individuals with more severely impaired metabolic health (e.g., T2DM, NAFLD, morbid obesity), who typically have elevated FGF21 levels and thus more room for improvement compared to individuals in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, circulating FGF21 levels have been reported to positively associate with BMI, body fat, liver fat content, blood pressure, insulin resistance (IR) and atherogenic lipid profiles [ 5 , 6 ], as well as predict incident metabolic syndrome and T2DM [ 7 , 8 ]. It is unclear whether and how weight loss and accompanying health improvements affect FGF21 levels, with some trials reporting reduced levels of circulating FGF21 upon diet-induced weight loss [ 9 , 10 , 11 , 12 , 13 ], and others reporting no effects on FGF21 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“… 70 On the contrary, an open-label randomized controlled trial (RCT) in overweight/obese individuals with NAFLD reported no effect of a calorie-restricted diet or a common (characterized as “healthy”) diet on both circulating FGF-21 and NAFLD. 74 These results warrant further research to definitely show whether the beneficial effect of lifestyle modifications on NAFLD 75 may be partly mediated by FGF-21, as well as whether there are distinct effects in different ages.…”
Section: Clinical Studiesmentioning
confidence: 94%
“… Change in circulating FGF-21 was positively associated with change in HFC. Asghari (2022) 74 Open-label RCT Overweight/obese with US-defined NAFLD (30) Overweight/obese with US-defined NAFLD (30) Calorie-restricted diet vs “healthy” diet 12 weeks No Effect of calorie- restricted diet on circulating FGF-21 and NAFLD. Circulating FGF-21 and hepatic steatosis remained unaffected after either diet.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Among them, 253 studies were excluded, including 51 studies in which the control group received other drugs, 16 studies which were non-RCTs, 13 studies in which no indicators were related to NAFLD, 79 studies in which the control group had other liver diseases, 74 studies which were reviews, and 20 studies which had incomplete data. In the end, 43 studies ( Pugh et al, 2013 ; Pugh et al, 2014 ; Abenavoli et al, 2015 ; Hallsworth et al, 2015 ; Dong et al, 2016 ; Panahi et al, 2016 ; Rahmani et al, 2016 ; Zhang et al, 2016 ; Abenavoli et al, 2017 ; Cheng et al, 2017 ; Houghton et al, 2017 ; Manzhalii et al, 2017 ; Misciagna et al, 2017 ; Navekar et al, 2017 ; Panahi et al, 2017 ; Dinu et al, 2018 ; Katsagoni et al, 2018 ; Wong et al, 2018 ; Ahn et al, 2019 ; Cai et al, 2019 ; Chashmniam et al, 2019 ; Ghaffari et al, 2019 ; Ghetti et al, 2019 ; Mirhafez et al, 2019 ; Saadati et al, 2019 ; Campanella et al, 2020 ; Cicero et al, 2020 ; Hariri et al, 2020 ; Nourian et al, 2020 ; Saberi-Karimian et al, 2020 ; Çevik Saldiran et al, 2020 ; Chong et al, 2021 ; Mirhafez et al, 2021 ; Mohamad Nor et al, 2021 ; Alami et al, 2022 ; Asghari et al, 2022 ; Chiurazzi et al, 2022 ; George et al, 2022 ; Khodami et al, 2022 ; Li et al, 2022 ; Mobasheri et al, 2022 ; Yurtdaş et al, 2022 ; Ezpeleta et al, 2023 ) were included in the NMA. The selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%